(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Human Resource Management (HRM) plays a strategic role in achieving institutional effectiveness and improving the quality of education. This study aims to analyze the benefits, scope, and recruitment process in optimizing HRM within educational institutions. The research method employed is library research with a qualitative descriptive approach, conducted through the analysis of relevant scientific literature such as books, journals, and recent studies. The findings indicate that optimizing HRM has a direct impact on improving teacher professionalism, organizational effectiveness, and institutional competitiveness. HRM contributes to enhancing educational quality, creating a positive work environment, strengthening collaborative culture, and aligning teacher competencies with the demands of the digital era. A transparent, competency-based recruitment process supported by information technology is a key factor in acquiring qualified and high-integrity educators. Therefore, professional and adaptive human resource management serves as the main foundation for building excellent, sustainable, and globally competitive educational institutions